Computer analysis of organelle translocation in primary neuronal cultures and continuous cell lines (The Rockefeller University Press, 1975)
Organelle translocation in a number of cell types in tissue culture as seen by high-resolution Zeiss-Nomarski differential interference contrast optics was filmed and analyzed by computer. Principal cell types studied included primary chick spinal cord, chick dorsal root ganglion, ratbrain, and various clones of continuous cell lines. Organelle translocations in all cell types studied exhibited frequent, large changes in velocity during any one translocation. The appearance of particles as seen with Nomarski optics was correlated with their fine structures in one dorsal root ganglion neurite by fixing the cell as it was being filmed and obtaining electron micrographs of the region filmed. This revealed the identity of several organelles as well as the presence of abundant neurotubules but no neurofilaments. Primary cell cultures exhibited more high-velocity organelle movements than continuous cell lines. The net progress of an organelle in a given direction was greater in primary neuronal cells than in fibroblasts or continuous cell lines. These findings are correlated with the literature on organelle translocation and axoplasmic transport.